Implementasi Strategi Pembelajaran Berbasis Masalah Pada Mata Pelajaran PAI Kelas X Di SMAN 1 Kecamatan Kapur IX - Nurul Aisyah; Charles Charles; Iswantir Iswantir; Arman Husni (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The background of this research is that not all students can understand this problem-based learning, and also not all students are able to think actively in solving problems that occur. Students are less enthusiastic in participating in learning and students who play around or don't focus on learning. From the problems that exist, the researcher is interested in studying the application of problem-based learning in Islamic Religious Education Class X at SMAN 1 Kapur IX District and its inhibiting factors. This study aims to find out how the application of this problem-based learning strategy and its inhibiting factors. This type of research is a descriptive qualitative research that describes problem-based learning strategies in Islamic Religious Education Class X at SMAN 1 Kapur IX District. In collecting data researchers used observation techniques, interviews and documentation. Meanwhile, to analyze it, the researcher uses data reduction, data presentation and conclusion drawing. Based on the results of the research conducted, the authors found that Islamic Religious Education teachers apply problem-based learning strategies starting from teacher planning in preparing lessons by making lesson plans which serve as teacher guidelines in teaching and learning activities carried out in the classroom. The application of problem-based learning strategies is carried out through three activities, namely preliminary activities, core activities and closing activities. The activity starts from the teacher entering the class by greeting, conditioning the class and then praying together after that the teacher explains the indicators and learning objectives. The core activities of student learning are given related to learning problems then students will observe and find solutions to the problems that occur. Closing activities at the end with the teacher and concluding student lessons, giving assignments and praying together. The inhibiting factors found were time allocation, students who were less able to solve problems that occurred and students playing games during learning.